A full-scale experimental investigation of passenger and freight train aerodynamics. (May 2020) - Soper, David; Baker, Chris
The movement of a train creates a disturbance to the air through which it passes, known as a slipstream. Such disturbances are characterised by changes in pressure, notably around the vehicle nose/tail, and a highly turbulent boundary growth along the vehicle side with an increasing slipstream velocity magnitude. Although these characteristic features occur in some form for all trains, the flow development associated with various train types can often be very different. Variability in train type makes it difficult to accurately characterise the aerodynamic effects of each individual train. In this paper, a detailed set of tests are undertaken to assess the aerodynamic flow development created around various train types common to the UK railway network. A comparison of the analysed data from different passenger and freight trains was made. The variability of freight train results was larger in comparison to the passenger trains examined, because of the large flow separations around the bluff freight train. Although the speed was lower for freight trains, the slipstream velocity and pressure magnitudes were larger than those observed for passenger trains. Passenger trains could be divided aerodynamically into two main types: long distance passenger trains and commuter trains. Longer train lengths were shown to increase the boundary layer growth: an important feature for long distance passenger trains as it creates an increase in the slipstream velocity peak magnitude at the train tail. Boundary layer stabilisation is not observed as in previous studies. The coupling of two carriage sets together, creating a large V-shaped region at the centre of the train, led to a clear step slipstream velocity peak coinciding with the change in pressure at the coupling region. Cross-correlation of results from measuring positions within the characteristic turbulent length scale range appeared to show similar results to autocorrelation time scales for larger scale separation of turbulent structures from the bogie and inter-carriage regions.